2023
DOI: 10.3389/fcvm.2023.1190069
|View full text |Cite
|
Sign up to set email alerts
|

Gout and hyperuricaemia: modifiable cardiovascular risk factors?

Abstract: Gout and hyperuricaemia are two clinical situations associated with an elevated risk of developing cardiovascular (heart failure, myocardial infarction, stroke) and metabolic and renal complications. One reason is probably related to the fact that the prevalence of hyperuricaemia and gout is high in clinical situations, which themselves involve a high cardiovascular risk, such as hypertension, diabetes, chronic kidney disease or obesity. However, recent studies suggest that hyperuricaemia may promote cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The recently reported preventive role of colchicine against atherosclerotic disease [1526], presumably via reduction of its contribution to inflammation and atherosclerosis, requires confirmation. This is required also for the CVprotective effect of reducing serum uric acid by antiuricemic agents, which has been suggested by earlier studies [1522,1524] but recently denied by a RCT with allopurinol in patients with CAD [1527,1528].…”
Section: Gout and Uric Acidmentioning
confidence: 99%
“…The recently reported preventive role of colchicine against atherosclerotic disease [1526], presumably via reduction of its contribution to inflammation and atherosclerosis, requires confirmation. This is required also for the CVprotective effect of reducing serum uric acid by antiuricemic agents, which has been suggested by earlier studies [1522,1524] but recently denied by a RCT with allopurinol in patients with CAD [1527,1528].…”
Section: Gout and Uric Acidmentioning
confidence: 99%
“…Previous articles have shown that oxidative stress might be of importance in the pathophysiology of BD. 14 Elevated SUA has been associated with mood-related disorders. Previous studies have found that the level of SUA in patients with depression and anxiety was lower than that in normal control; and the severity and duration of symptoms were negatively associated with uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…HUA is not only the pathological underlying cause of gout but is also an independent risk factor for obesity, 4 , 5 hypertension, 6 , 7 diabetes, 8 dyslipidemia, 9 , 10 liver dysfunction, 11 kidney dysfunction, 12 metabolic syndrome 13 and cardiovascular disease. 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 HUA is widely recognised as the primary cause of gout onset and is also associated with several health consequences, including hypertension, diabetes, metabolic syndrome (MetS), liver dysfunction, kidney dysfunction and cardiovascular disease. [3][4][5][6][7][8][9][10][11] Therefore, it is critical to understand the SUA level and the prevalence of HUA in community healthcare and health policymaking.…”
Section: Introductionmentioning
confidence: 99%